2021
DOI: 10.17533/udea.mut.v14n2a05
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant Reviews in Brazil and the USA: A Feast of Cultural Differences and Their Impact on Translation

Abstract: This article shares the findings from a study aimed to create a bilingual English-Portuguese glossary of terms and collocations characteristic of restaurant reviews, especially concerning the search for transla­tion equivalents. Relying on the assumptions of corpus linguistics, we conducted both quantitative and qualitative analyses to investigate a comparable corpus of texts published in the United States and Bra­zil. The manual investigation of simple and compound keywords retrieved with Sketch Engine showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For analysis, we used Sketch Engine, an online corpus tool founded by Adam Kilgarriff, who collaborated with Pavel Rychlý from Masaryk University (Kilgarriff et al, 2014). Sketch Engine has been proven as a reliable instrument in critical discourse studies to investigate environmental discourses, as found in copper mining discourse (Poole, 2018), rhino poaching in South Africa (Engelbrecht, 2020), political election discourse (Melendres and Barea, 2021; Vollmer, 2017), and tourism discourse (Rebechi et al, 2021;Srdanović, 2020). Those studies use common tools: word lists, keywords, collocation, and concordances.…”
Section: Discussionmentioning
confidence: 99%
“…For analysis, we used Sketch Engine, an online corpus tool founded by Adam Kilgarriff, who collaborated with Pavel Rychlý from Masaryk University (Kilgarriff et al, 2014). Sketch Engine has been proven as a reliable instrument in critical discourse studies to investigate environmental discourses, as found in copper mining discourse (Poole, 2018), rhino poaching in South Africa (Engelbrecht, 2020), political election discourse (Melendres and Barea, 2021; Vollmer, 2017), and tourism discourse (Rebechi et al, 2021;Srdanović, 2020). Those studies use common tools: word lists, keywords, collocation, and concordances.…”
Section: Discussionmentioning
confidence: 99%